From Stoichiometric Reagents to Catalytic Partners: Selenonium Salts as Alkylating Agents for Nucleophilic Displacement Reactions in Water. Issue 1 (27th October 2021) - Martins, Nayara Silva; Ángel, Alix Y. Bastidas; Anghinoni, João M.; Lenardão, Eder J.; Barcellos, Thiago; Alberto, Eduardo E.
Abstract: The ability of chalcogenium salts to transfer an electrophilic moiety to a given nucleophile is well known. However, up to date, these reagents have been used in stoichiometric quantities, producing a substantial amount of waste as byproducts of the reaction. In this report, we disclose further investigation of selenonium salts as S‐adenosyl‐L‐methionine (SAM) surrogates for the alkylation of nucleophiles in aqueous solutions. Most importantly, we were able to convert the stoichiometric process to a catalytic system employing as little as 10 mol % of selenides to accelerate the reaction between benzyl bromide and other alkylating agents with sodium cyanide in water. Probe experiments including 77 Se NMR and HRMS of the reaction mixture have unequivocally shown the presence of the selenonium salt in the reaction mixture. Abstract :